(untitled) (Docentes 2.0 Journal, 2025)
Administrative management (AM), based on innovation, knowledge culture, and organizational sustainability, influences job satisfaction (JS). Furthermore, its strengthening generates public value, loyalty, and trust; consequently, it achieves suitability and guarantees in the services offered. The objective was to determine the influence of administrative management on employee job satisfaction at a Peruvian management entity. The methodology was based on the positivist paradigm, a hypothetical-deductive method, a quantitative approach, a non-experimental correlational-causal-comparative design, and a cross-sectional analysis. The sample consisted of 100 employees. Two validated questionnaires were administered: Administrative Management, composed of 22 items divided into the following dimensions—planning, organization, direction, and control (? = .74)—and Job Satisfaction, which comprised intrinsic and extrinsic satisfaction dimensions (? = .867). The results, as indicated by the Nagelkerke coefficient (.616), revealed that job satisfaction varies by 61.6% depending on administrative management. Likewise, the dependence on the other components was confirmed (51%, 41.7%, 37.4%, 20.4%). Consequently, it is possible to reduce risks that affect the efficiency and quality of educational services, as well as challenges to decent work, especially those related to inequality, discrimination, job instability, dropout rates, and occupational health and safety. It was concluded that it is necessary to consolidate administrative control based on tactical, strategic, operational, financial, security, and sustainability axes. These will have a positive impact on the revaluation of the educational social pact.